Bibliographic review on drug intoxication in Brazil (Research, Society and Development, 2022)
Drug intoxication can occur in several ways, and that is one of the main reasons that impair the pharmacotherapy of patients. This work is a literature review that aims to identify which drug classes caused more drug intoxications between the period of 2000 and 2020. Methodology: Integrative literature review by selecting articles through inclusion and exclusion criteria. Results: Benzodiazepines were the most prevalent therapeutic class, followed by antidepressants, antibiotics and nonsteroidal anti-inflammatory drugs, in higher frequency in cases involving women, between the age group of 20 to 29 years. Among the drugs usually cited in intoxication are clonazepam, amitriptyline, paracetamol, and carbamazepine. Conclusion: The analysis of the articles pointed to the benzodiazepine class of drugs as the main causative agents of drug intoxication in Brazil, making it necessary to take toxicovigilance measures in order to reduce the number of intoxication cases, in addition to encouraging the pharmaceutical professional to explain the risks of using the drug.